Prevalence of Diarrhea and Associated Factors among Under Five Years Children in Harena Buluk Woreda Oromia Region, South East Ethiopia, 2018 - Solomon Getahun Beyene; Abulie Takele Melku (Journal of Public Health International, 2018)
Background: Acute diarrheal diseases are the leading cause of preventable childhood death, especially in developing countries. It is the second leading cause of death in under-five year children nest to pneumonia. Objectives: The aim of this study was to determine the magnitude and associated factors of diarrhea in under-five in Harena Buluk district. Methods: A community based Cross sectional study was conducted in February, 2018. A two stage stratified sampling method was done to select the eligible households. Data was collected by trained data collectors using pretested questionnaire list which was prepared based on EDHS and WHO core questionnaires related to diarrhea. Data was entered in to a computer using Epi data 3.1 and exported to SPSS V.20 for further analysis. Logistic regression was used to determine level of association with 95% CI. A p-value <0.05 in the final model were considered as significant. Result: The two weeks period magnitude of diarrhea among under-five children was 28.4% with 95% CI (14.5-20.8) which was associated with households with one under five children (AOR: 0.268, 95% CI(.08,0.90)), living in the home with single room ((AOR = 6.01, 95% CI(1.01,36.01)), clean latrine/faces not seen around the pit or on the floor of latrine(AOR: 0.298, 95% CI(0.097,0.92)), long time take to fetch water from source (AOR: 0.046,95%CI(0.01,0.22)), home based water treatment ((AOR = 0.15, 95% CI: (0.04, 0.62)), living with animal in the same house(AOR: 8.31, 95% CI(2.46,28.06)), children who took gruel type of food(AOR: 0.24, 95% CI(0.07,0.81)), hand washing practice before cooking food (AOR: 0.195(0.066, 0.574)). Conclusion: The two weeks period magnitude of acute under-five diarrhea was relatively high and number of under five children in the household, cleanness latrine, time taking from the source of water, home based water treatment, number of rooms in the home, live with animal in the same house, type of food child take, hand washing before food preparation had significant association with the occurrence of under-five diarrhea. Improve community about home and environmental sanitation and hand practices were recommended.
Keywords: Acute diarrhea